2004
DOI: 10.1093/carcin/bgh146
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced invasiveness of breast cancer cell lines upon co-cultivation with macrophages is due to TNF-  dependent up-regulation of matrix metalloproteases

Abstract: Apart from the neoplastic cells, malignant tumours consist of the extracellular matrix (ECM) and normal cells, in particular tumour-associated macrophages (TAM). To understand the mechanisms by which TAM can influence tumour cell invasion we co-cultured the human breast cancer cell lines MCF-7, SK-BR-3 and the benign mammary epithelial cell line hTERT-HME1 with macrophages. Co-incubation enhanced invasiveness of the tumour cells, while hTERT-HME1 remained non-invasive. Addition of the broad-spectrum matrix met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
258
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(283 citation statements)
references
References 36 publications
18
258
1
6
Order By: Relevance
“…When THP-1 cells were co-cultured with MCF-7, a representative breast cancer cell line, Western blotting analysis revealed an increase in Akt phosphorylation at both 308 and 473 residues, suggesting that breast cancer cells can stimulate Akt activation in macrophage (Fig. 1B) [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When THP-1 cells were co-cultured with MCF-7, a representative breast cancer cell line, Western blotting analysis revealed an increase in Akt phosphorylation at both 308 and 473 residues, suggesting that breast cancer cells can stimulate Akt activation in macrophage (Fig. 1B) [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…When THP-1 cells were co-cultured with MCF-7, a representative breast cancer cell line, Western blotting analysis revealed an increase in Akt phosphorylation at both 308 and 473 residues, suggesting that breast cancer cells can stimulate Akt activation in macrophage (Fig. 1B) [21,22].A small RNA interference plasmid, containing a green fluorescent protein expression cassette, was chosen from our previous experiments to disrupt Akt2 expression in MDA-MB-231 cells [23]. After selection by 0.6 mg/mL Hygromycin B for 4 wk, cells were examined by Western blotting analysis of Akt2 and designated as siAkt2/THP-1 cells.…”
mentioning
confidence: 99%
“…Although generally known for their tumoricidal capacity, there is growing evidence that regulatory networks within tumor tissues redirect their function into a tumor-promoting activity. We have recently shown that cocultivation with M increases invasiveness of weakly invasive breast cancer cells (33). The aim of this study was to investigate whether Wnt signaling is involved in this effect.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro co-culture of macrophages with tumor cells has been shown to result in accelerated tumor growth [49]. TAMs express several factors, such as EGF, MMP-9, TGF-β and CXCL-14, that stimulate tumor cell proliferation and survival [50,51].…”
Section: Discussionmentioning
confidence: 99%